Optimality and Element Theory: The case of initial fricative voicing in Southern Old and Middle English - 최재혁 (Studies in Phonetics, Phonology, and Morphology, 2016)
This study examines the nature of consonant weakening processes (i.e. lenition) within the framework of Optimality Theory. In order to delve into the current topic more deeply, the voicing of initial fricatives particularly in the southern and south-western dialects of Old and Middle English is investigated. I argue that the *COMPLEX[Element] constraint, where ‘element’ refers to one of the primitives of Element Theory, plays a central role in analysing weakening processes within this theoretical framework. In addition, it is demonstrated that lenition processes such as the voicing of consonants can be accounted for within the constraint interaction between positional faithfulness constraints such as IDENT[element] and the integrated constraint *COMPLEX[Element] which I propose. KCI Citation Count: 0